Acoustofluidic Relay: Sequential Trapping and Transporting of Microparticles via Acoustically Excited Oscillating Bubbles. (April 2014) - Xie, Yuliang; Ahmed, Daniel; Lapsley, Michael Ian; Lu, Mengqian; Li, Sixing; Huang, Tony Jun
We report an on-chip acoustofluidic method for sequential trapping and transporting of microparticles via acoustically oscillating bubbles. The size and location of bubbles were precisely controlled by lithography. When the acoustic waves were turned off, particles followed the streamlines dictated by laminar flow. When the acoustic waves were turned on, particles were attracted to and trapped in a vortex near the surface of bubble. Therefore, particles could move across the microfluidic channel with programmed trajectories. Additionally, a theoretical model based on acoustic radiation force and drag force due to acoustic microstreaming was established to help design this particle-trapping and -transporting system.